Mathematical journeys - Schumer, Peter D. (Wiley-Interscience, 2004)
Each chapter of the book focuses on some interesting piece of mathematics, giving the history and requisite math background, the solution of a problem or two, and some indication of natural generalizations and related areas of study. Whether you’re a math novice curious to learn what your calculus class left out or a math lover ready for the green chicken contest, Mathematical Journeys will give you a true taste of what mathematicians themselves find most exciting about math.